De novo synthesis of mesoporous photoactive titanium(iv)–organic frameworks with MIL-100 topology. Issue 15 (19th March 2019) - Castells-Gil, Javier; M. Padial, Natalia; Almora-Barrios, Neyvis; da Silva, Ivan; Mateo, Diego; Albero, Josep; García, Hermenegildo; Martí-Gastaldo, Carlos
Abstract : The development of new titanium frameworks remains limited by the difficulties in forming persistent Ti clusters amenable to the isoreticular approach. MIL-100(Ti) combines a mesoporous structure with excellent chemical stability and photoactivity from the reticulation of Ti3 (μ3 -O) metal-oxo clusters. Abstract : Most developments in the chemistry and applications of metal–organic frameworks (MOFs) have been made possible thanks to the value of reticular chemistry in guiding the unlimited combination of organic connectors and secondary building units (SBUs) into targeted architectures. However, the development of new titanium-frameworks still remains limited by the difficulties in controlling the formation of persistent Ti-SBUs with predetermined directionality amenable to the isoreticular approach. Here we report the synthesis of a mesoporous Ti-MOF displaying a MIL-100 topology. MIL-100(Ti) combines excellent chemical stability and mesoporosity, intrinsic to this archetypical family of porous materials, with photoactive Ti3 (μ3 -O) metal-oxo clusters. By using high-throughput synthetic methodologies, we have confirmed that the formation of this SBU is thermodynamically favored as it is not strictly dependent on the metal precursor of choice and can be regarded as an adequate building block to control the design of new Ti-MOF architectures. We are confident that the addition of a mesoporous solid to the small number of crystalline, porous titanium-frameworks available will be a valuable asset to accelerate the development of new porous photocatalysts without the pore size limitations currently imposed by the microporous materials available.